Survey on Characteristics of Processing and Quality of Dangke Milk Cows in Enrekang District, South Sulawesi - W. Hatta; M. B. Sudarwanto; I. Sudirman; R. Malaka (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
The development of the processing industry of dangke milk cows in Enrekang district had an important role in support of the improvement of national milk consumption and absorption of milk cows of local farmers. The purpose of research is to describe of the characteristics of the processing of dangke milk cows consisting of methods of manufacture and storage, as well as the quality of dangke in Enrekang district. This research is a descriptive survey. The respondents are 60 people manufacturers dangke milk cows which selected by simple random sampling. Data on the characteristics of dangke processing collected through observation and interviews with open-ended questionnaire, whereas quality of dangke (moisture, fat, protein, ash, and pH) were measured by AOAC method (1995). Data were analyzed with descriptive statistics. Conclusion of this study is that the method of manufacture of dangke milk cows includes heating of the milk, the addition of papaya latex solution, filtering and printing of the curd, and packaging products are varied quantitatively cause the quality of dangke is diverse. Dangke storage method allows a reduction of the quality of the physical and microbiological dangke milk cows.